Unveiling the effects of Rosa canina oligosaccharide liposome on neuropathic pain and motor dysfunction following spinal cord injury in rats: relevance to its antioxidative effects - Ahmadpour, Yasaman; Bahrami, Gholamreza; Arkan, Elham; Abbaszadeh, Fatemeh; Aghaz, Faranak; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundSpinal cord injury (SCI) is a leading cause of sensorimotor disorders, impacting millions of people globally. The absence of effective treatments and the side effects of existing medications highlight the need for innovative research into new therapeutic compounds.PurposeGiven the critical role of oxidative stress in the development of SCI and the antioxidant properties of oligosaccharides in other neurological disorders, this study focuses on the role of oxidative stress in SCI and explores the potential of a novel oligosaccharide nanoformulation derived from Rosa canina (Oligo-L).Materials and methodsOligo-L was formulated using soy lecithin as the phospholipid and the characterization included size, zeta potential, morphology, and drug loading efficiency. Then 35 Wistar male rats were divided into five groups of Sham, SCI, and Oligo-L (10 μL intrathecal injection of 15, 30, and 45 mg/mL). An aneurysm clip was used to induce compression injury of the SCI and Oligo-L groups. Sensory-motor functions were evaluated weekly for 4 weeks using tests such as the BBB scale, inclined plane, acetone drop, hot plate, von Frey, and monitoring of weight changes. Additionally, oxidative stress markers and histological changes were examined to evaluate changes in nitrite, glutathione, catalase, and neuronal survival.Results and discussionThe findings indicated that Oligo-L treatment led to significant improvements in neuropathic pain, and motor function performance and weight of the animals from the first week post-SCI. Oligo-L also enhanced catalase and glutathione levels while reducing serum nitrite levels, contributing to neuronal preservation. Additionally, Oligo-L increased neuronal survival in the both ventral (motor neurons) and dorsal (sensory neurons) horns of the spinal cord.ConclusionOverall, Oligo-L, characterized by its beneficial physicochemical properties, showed promising potential as a neuroprotective agent and facilitated the recovery of sensory and motor functions after SCI.